2005
DOI: 10.1111/j.1365-2559.2005.02299.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic potential of ductal carcinoma in situ (DCIS) of human breast

Abstract: The significantly inverse correlation between HER1/EGFR and comedo-type DCIS and the observation that VEGF and the other angiogenic factors tested are independent of HER2 overexpression, suggest that progression of comedo-type DCIS and angiogenesis in breast carcinoma are not regulated via the HER1/EGFR or HER2 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
3
12
0
2
Order By: Relevance
“…The degree of angiogenesis was variable and strongly related to the degree of vascular endothelial growth factor (VEGF) expression. High grade DCIS was more often associated with a strong VEGF expression than low grade lesions, which was also observed by Vogl et al [29]. However, these differences in VEGF expression between low grade and high grade lesions were not statistically significant.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The degree of angiogenesis was variable and strongly related to the degree of vascular endothelial growth factor (VEGF) expression. High grade DCIS was more often associated with a strong VEGF expression than low grade lesions, which was also observed by Vogl et al [29]. However, these differences in VEGF expression between low grade and high grade lesions were not statistically significant.…”
Section: Discussionsupporting
confidence: 74%
“…The process of angiogenesis is stimulated by growth factors such as vascular endothelial growth factor (VEGF) and plateletderived endothelial growth factor/thymidine phosphorylase (PD-ECGF/TD) released into the stroma by tumor and immune cells [29,30]. Vogl et al [29] found PD-ECGF/TP to be present in all cases of DCIS, without a significant correlation with the DCIS subtype. In the study of Guidi et al [30], in 84% of the cases of DCIS microvessel density was more prominent than in benign tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The central necrotic areas are interpreted as an indication that the neoplastic cells are growing faster and that there is therefore a higher risk of progression to invasive carcinoma. 41,42 The comedo appearance was mentioned in the WHO classification as a feature occasionally detectable in CMC in situ. 27 Those comedocarcinomas identified in the present study were not in situ lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It involves the process of endothelial cell activation, degradation of the basement membrane and extracellular matrix, with migration and proliferation of endothelial cells. It has been associated with overexpression of estrogen and progesterone receptors (Vamesu, 2008), progression from ductal carcinoma in-situ (Vogl et al, 2005), metastasis (Weidner (Karelia et al, 1997;JanShow et al, 1998;Nazan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%